Unraveling the Pedagogical Conundrum: Teaching Reading as a Complex Challenge - Nazarova Shoiraxon Abdumo‘min qizi (Journal of Science-Innovative Research in Uzbekistan, 2024)
This comprehensive article explores the intricate challenges faced by educators in the realm of teaching reading. The author skillfully navigates through the diverse landscape of learners, acknowledging the heterogeneity of student abilities, backgrounds, and learning styles. The article delves into the perpetual debate between phonics and whole language instruction, highlighting the ongoing struggle for a balanced approach. A notable aspect of the article is its recognition of the impact of technology on literacy instruction. The discussion around the integration of digital tools in the 21st-century classroom adds depth to the exploration of pedagogical challenges, acknowledging the potential benefits and pitfalls of technology in reading education. Furthermore, the article emphasizes the pivotal role of reading comprehension in literacy development. By addressing the multifaceted nature of comprehension and proposing various strategies, the author underlines the importance of going beyond decoding skills to foster a deeper understanding and appreciation for written text. Socioeconomic factors are adeptly woven into the narrative, acknowledging the significant impact of societal disparities on literacy development